Hubungan Jumlah Tenaga Administrasi Manajemen Dan Sarana Prasarana Dengan Keterlambatan Dan Ketidaklengkapan Sistem Pencatatan Dan Pelaporan Terpadu Puskesmas (SP2TP) Di Puskesmas SeKabupaten Banjar Tahun 2016 - Firyal Yasmin; Sugeng Riyanto; Muhammad Rifani (Jurnal Kesehatan Indonesia, 2016)
Public Health Center is unity functional organization that organizes health effort that is comprehensive, integrated, equitable acceptable and affordable by the community with the active participation of communities and use the results of the development of science and appropriate technology, at a cost that can be borne by the government and the wider community in order to achieve optimal health status, without neglecting the quality of services to individuals. Public Health Center should Recording and Reporting System of Integrated Health Centers each month to the Banjar District Health Office. When examined in the feed back SP2TP, it turns out there are incomplete and late reporting Recording and Reporting System of Integrated Health Centers (SP2TP). This study aims to determine Tardiness And Incompleteness Recording System And Unified ReportIng Public Health Center In Banjar District Public Health Center In 2016. This study uses an analytical method Correlation Reseach design. This study was conducted to 23 public health centers in Banjar District Health Office by statistik test. The results on several variables by using the chi-square shows that there’s no correlation of the numbers of workers management administration and infrastructure with tardiness and incompleteness recording system and unified reporting public health center in Banjar District Public Health Center In 2016